Studi komparasi persepsi wisatawan terhadap implementasi experiential marketing pada hotel berbintang dan non bintang di kawasan pariwisata candidasa kabupaten karangasem bali - Mirayani, Ni Kadek Sri; Arismayanti, Ni Ketut; Widyatmaja, I Gusti Ngurah (Jurnal Kepariwisataan dan Hospitalitas, 2018)
In globalization era, experience becomes important in carrying out the accommodation business. Karangasem regency has 992 accommodation but the number of tourist arrivals still in hundreds thousands each year. Therefore, every hotel strives to provide a memorable experience to tourists through an experiential marketing. The experience received by tourists during their stay in accomodation is only based on the view of the hotel without knowing the opinions of tourists so it is important to know the perception of tourists to the experience that has been received. The research location is located in the Candidasa Tourism District with comparisons in star hotels and non star hotels. The variable used is strategic experiential modules with five indicators are sense, feel, think, act and relate. Data obtained through observation, questionnaire and literature study. The number of respondents reached 200 respondents consisting of 100 respondents stay in star hotels and 100 respondents stay in non-star hotels. The collected data were analyzed using qualitative and likert analysis. The results is known that the implementation of experiential marketing in star hotels more successful than non star hotels. Tourists who stayed at star hotels give Strongly Agree category for each indicator. At non star hotel, the tourists who stayed gives the value with the Agree category for the feel indicator while the sense, think, act and relate indicator are only in the Neutral category. Threfore, star hotel should mantain their experience or increase it. While non star hotel should increase their experience. Keywords : Tourists Perception, Experiential Marketing, Star  Hotels, Non-star Hotel